Surface tension and refractive index of pure and water-saturated tetradecyltrihexylphosphonium-based ionic liquids - Almeida, Hugo F. D.
Experimental data on the surface tension and refractive index of tetradecyltrihexylphosphonium-based ionic liquids with bromide, chloride, decanoate, methanesulfonate, dicyanimide, bis(2,4,4-trimethylpentyl)phosphinate and bis(trifluoromethylsulfonyl)imide anions are reported. The data were obtained for pure and water saturated samples at temperatures from 283 K to 353 K and at atmospheric pressure. The refractive index of the investigated ionic liquids decreases with increasing the water content in the sample. On the other hand, no clearly dependence of the surface tension with the water content up to a weight fraction of 16% was found. The prediction of the refractive index for the studied ionic liquids was also accomplished by a group contribution method and new values for the cation and diverse anions were estimated and proposed. The studied ionic liquids show lower surface tension in comparison with imidazolium-, pyridinium-or pyrrolidinium-based ionic liquids with a similar anion; also they show higher surface entropy than cyclic nitrogen-based fluids which indicates a lower surface organization. The anion dependence of the surface tension and surface entropy for the investigated ionic liquids is weaker than that for short-chain imidazolium-based ionic liquids. Their critical temperatures evaluated from Eotvos and Guggenheim equations are also lower than those of N-heterocyclic ionic fluids. (C) 2012 Elsevier Ltd. All rights reserved.